Interstitial 6q25 microdeletion syndrome: ARID1B is the key gene. Issue 5 (11th January 2016) - Ronzoni, Luisa; Tagliaferri, Francesco; Tucci, Arianna; Baccarin, Marco; Esposito, Susanna; Milani, Donatella
Abstract : Interstitial deletions of the long arm of chromosome 6 are rare. Clinically, these deletions are considered to be part of a unique microdeletion syndrome associated with intellectual disability and speech impairment, typical dysmorphic features, structural anomalies of the brain, microcephaly, and non‐specific multiple organ anomalies. The critical region for the interstitial 6q microdeletion phenotype was mapped to 6q24–6q25, particularly the 6q25.3 region containing the genes ARID1B and ZDHHC14 . It has been hypothesized that haploinsufficiency of these genes impairs normal development of the brain and is responsible for the phenotype. This case report describes a girl presenting with typical features of 6q microdeletion syndrome, including global developmental delay, speech impairment, distinct dysmorphic features, dysgenesis of the corpus callosum, common limb anomalies, and hearing loss. Chromosome analysis by array‐CGH revealed a small interstitial 6q deletion spanning approximately 1.1 Mb of DNA and containing only one coding gene, ARID1B . We suggest that ARID1B is the key gene behind 6q microdeletion syndrome, and we discuss its possible role in the phenotypic manifestations. © 2016 Wiley Periodicals, Inc.